2005
DOI: 10.4103/0019-5545.43063
|View full text |Cite
|
Sign up to set email alerts
|

Management of trichotillomania

Abstract: Hallopeau, a French dermatologist, coined the term trichotillomania (TM) to describe alopecia (baldness) caused by self-traction of the hair, but the term now encompasses the entire syndrome of pathological hair-pulling. It is a disorder of impulse control. The authors present three (adult and child) cases of TM managed successfully using a combination of pharmacotherapy and a package of behaviour therapy. Some psychopathological aspects of the disorder are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…SSRIs such as fluoxetine have already been implicated in the management of trichotillomania, and this further elaborates their effectiveness in FTD as well. [ 4 6 12 ] The role of early identification of SIBs such as trichotillomania and skin excoriation can result in the early initiation of treatment as well as aid in the exploration of the use of N-acetyl cysteine and even potential use of habit reversal and behavioral therapies including yoga therapy, especially in the initial stage of this dementia.…”
Section: Discussionmentioning
confidence: 99%
“…SSRIs such as fluoxetine have already been implicated in the management of trichotillomania, and this further elaborates their effectiveness in FTD as well. [ 4 6 12 ] The role of early identification of SIBs such as trichotillomania and skin excoriation can result in the early initiation of treatment as well as aid in the exploration of the use of N-acetyl cysteine and even potential use of habit reversal and behavioral therapies including yoga therapy, especially in the initial stage of this dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Various other studies explored insight oriented psychotherapy, cognitive-behavioral therapy but documented three studies in this report showed very encouraging results in managing this disorder of impulse control. [ 35 ]…”
Section: Case Reportsmentioning
confidence: 99%
“…In a more recent paper, Kaur et al . [ 33 ] reported three cases of trichotillomania treated with pharmacotherapy and BT consisting of JPMR, deep breathing exercise, distraction technique, response prevention, thought stopping and diary maintenance. Improvement occurred in all cases in three to four weeks.…”
Section: Introductionmentioning
confidence: 99%